2008
DOI: 10.1186/1756-3305-1-26
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium knowlesi in humans, macaques and mosquitoes in peninsular Malaysia

Abstract: Background: Since a large focus of human infection with Plasmodium knowlesi, a simian malaria parasite naturally found in long-tailed and pig tailed macaques, was reported in Sarawak, Malaysian Borneo, it was pertinent to study the situation in peninsular Malaysia. A study was thus initiated to screen human cases of Plasmodium malariae using molecular techniques, to determine the presence of P. knowlesi in non-human primates and to elucidate its vectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
270
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(278 citation statements)
references
References 26 publications
5
270
0
3
Order By: Relevance
“…Identification of more cases in the following years from different hospitals in Sarawak (Cox- , high incidence in the interior divisions of Sabah (Lau et al 2011) and severe cases from a tertiary hospital in Sabah (Willam et al 2011) established that the entire Malaysian Borneo has P. knowlesi cases. Vythillingam et al (2008) reported cases from Peninsular Malaysia.…”
Section: Natural P Knowlesi Infections In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of more cases in the following years from different hospitals in Sarawak (Cox- , high incidence in the interior divisions of Sabah (Lau et al 2011) and severe cases from a tertiary hospital in Sabah (Willam et al 2011) established that the entire Malaysian Borneo has P. knowlesi cases. Vythillingam et al (2008) reported cases from Peninsular Malaysia.…”
Section: Natural P Knowlesi Infections In Humansmentioning
confidence: 99%
“…These investigators used Anopheles balabacensis, a member of the Leucosphyrus complex placed under the Leucosphyrus Group (Sallum et al 2005). The proof that P. knowlesi in humans is a case of malaria zoonoses came from studies by Vythillingam et al (2006Vythillingam et al ( , 2008. In Sarawak Lee et al (2011) Malaysia, specimens of An.…”
Section: Clinical Symptoms Of P Knowlesi Infections and Treatmentmentioning
confidence: 99%
“…To our knowledge this is the first report of the detection of P. knowlesi together with P. falciparum and P. vivax in an individual mosquito from a population that acts as the principal human malaria vector in a given area. Studies on P. knowlesi transmission in Malaysia (Vythilingam et al, 2006(Vythilingam et al, , 2008 identified a vector species that, although belonging to the Anopheles leucosphyrus group, is at present not implicated in the transmission of human malaria parasites. Our report shows that P.…”
mentioning
confidence: 99%
“…Detection of the CSP gene of P. knowlesi was carried out as previously described (Vythilingam et al, 2008). Primer sequences for region 3 of pfg377 mRNA and gDNA (Menegon et al, 2000), pfs16 mRNA (Niederwieser et al, 2000), ssrRNA-DNA of human Plasmodium spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation